RUSSIA’S FALIN–KVITSINSKY ENERGY DOCTRINE: HISTORY AND EXPERIENCE APPLYING TO SELECTED CENTRAL EUROPEAN COUNTRIES - Mróz, Maciej; Paszkowski, Michał (Torun International Studies, 2023)
This article discusses the evolution of the energy security of Belarus, Estonia, Latvia, Lithuania, Poland and Ukraine since the collapse of the Union of Soviet Socialist Republics (USSR), in terms of natural gas supplies. Instead of framing energy dependencies on Russia in a descriptive way, this article shows the empirical validation of the Falin–Kvitsinsky doctrine, which includes the use of energy resources as tool in foreign policy. Therefore, the authors propose a three-element Falin–Kvitsinsky doctrine indicator to measure the power of this doctrine using the yearly data for 1991–2021. Authors argue that the impact of this doctrine should be assessed through the lens of energy supply security and then measured by appropriate indicators. This approach might be seen as opposite to the mainstream publications which are mostly descriptive in this field. In the article, the authors provided clear evidence of the Falin–Kvitsinsky doctrine existence until the end of 2021, which was applied during the Russian-Ukrainian war. Actions taken by Russia over the years were aimed at making Central European countries dependent on natural gas supply, which would then prompt these countries to limit their aid to Ukraine during the conflict that began in 2022. In conclusion, Russia is able to pursue its political goals in the manner suggested by the Falin–Kvitsinsky doctrine as long as each Central European country tries to ensure its own energy security. However, the Falin-Kvitsky doctrine did not fully meet its objectives, as Central European countries, as a result of the Russian-Ukrainian war, were able to quickly take steps to diversify the sources and directions of natural gas supplies by taking comprehensive measures and strengthening cooperation.